Utilization of Recycled Aggregates in Fly Ash-Based Geopolymer Concrete for Pavement Construction - Venkatesh chittem; Dr.G Kalyani; Maheswararao; R, Sabharinadh. B (Utilitas Mathematica, 2025)
The utilization of recycled aggregates in construction materials has garnered significant attention due to its environmental and economic benefits. This study investigates the feasibility of incorporating recycled concrete aggregates (RCA) as substitutes for natural aggregates in fly ash-based geopolymer concrete for pavement construction. This study investigates the utilization of recycled concrete aggregates (RCA) in geopolymer concrete for potential pavement applications. The performance of geopolymer concrete incorporating various levels of RCA (10%, 20%, 30%, and 40%) as replacements for natural aggregates was evaluated in terms of compressive strength, water absorption, abrasion resistance, and chloride ion permeability. The results showed that the compressive strength of geopolymer concrete decreased gradually as the RCA content increased, with mixes containing up to 20% RCA maintaining sufficient strength for pavement use. Water absorption and volume loss due to abrasion increased with higher RCA percentages, indicating greater porosity and reduced durability. The chloride ion permeability test revealed higher charge passage with increasing RCA content, suggesting increased permeability, but all mixes still exhibited low chloride ion permeability, indicating adequate resistance to chloride-induced corrosion. These findings demonstrate that while the use of RCA in geopolymer concrete can lead to a slight reduction in strength and durability, it remains a viable and sustainable option for pavement construction, especially when RCA replacement levels are kept below 20%.